Literature Study of Multiple Intelligences Implementation on Learning Outcomes in Elementary Schools: Studi Literatur Implementasi Multiple Intelligences Terhadap Hasil Balejar di Sekolah Dasar - Nur Maulidiyah; Vanda Rezania (Universitas Muhammadiyah Sidoarjo, 2021)
This study is intended to describe the implementation of Multiple Intelligences on learning outcomes in elementary schools. This research is included in qualitative research with the type of literature study research (Literature Review). There are four stages in this research, among others are; organize, synthesize, identify and formulate questions that require further research. The results of the research show that the implementation of Multiple Intelligences on learning outcomes in elementary schools can be applied to the learning process which includes; strategies, models, learning methods. the implementation of Multiple Intelligences on learning outcomes in elementary schools can be applied by all educators and education personnel, both teachers and principals. The implementation of Multiple Intelligences in elementary schools is also a new breakthrough in the education system in Indonesia because Multiple Intelligences is an education system that empowers students. There are 9 types of intelligence, including; linguistic, logical-mathematical, visual-spatial, kinesthetic, interpersonal, intrapersonal, musical, naturalistic and existential.